Application of Bioactive Compound from Plants Herb and Chaetomium spp. against Colletotrichum musae Causal Anthracnose Postharvest Disease of Banana - SIBOUNNAVONG, Phonesavard; PHENGKHAMMA, Tiengngern; SOULIYA, Oupasoth; THIKEO, Satheun; KHEMMARATH, Sitha; SIBOUNNAVONG, Phoutthasone (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
Testing of Bioactive Compound from Plants Herb and Chaetomium spp. against Colletotrichum musae Causal Anthracnose Postharvest Disease of Banana, the purpose of this research to isolation Colletotrichum musae, morphology study and pathogenicity test, to testing crude extracts from Aloe vera, Turmeric, Ch. globosum and Ch. cupreum to inhibited C. musae SKU-1 caused anthracnose of banana postharvest disease in-vitro by Food Poisoned Techniques and to testing mixed all crude extracts from herbs and Chaetomium spp to inhibited C. musae SKU-1 caused anthracnose of banana postharvest disease, the experimental design using by two factors factorial in Completely Randomized Design with 4 replications. The results founded that an isolate of Colletotrichum from anthracnose postharvest disease of banana fruit sample collected in Sepon district, Savannakhet province Lao PDR was identified as Colletotrichum muase by morphology techniques, it is the first time C. musae is reported as the causal pathogen of anthracnose postharvest disease of banana fruit in Lao PDR. testing crude extracts from Aloe vera, Turmeric, Ch. globosum and Ch. cupreum were investigated to control C. musae SKU-1 in in-vitro test, all the crude extracts from Aloe vera, Turmeric, Ch. globosum and Ch. cupreum significantly inhibited mycelial growth and conidial production of C. musae SKU-1 as crude EtOAc of Aloe vera and Turmeric were more effective in conidial inhibition of pathogen than crude hexane and MeOH, the effective dose (ED50) were 2.011mg/ml and 2.219mg/ml respectively. Also crude EtOAc of Ch. globosum was more effective in conidial inhibition of pathogen than other, the effective dose (ED50) was 0.06mg/ml and Ch. cupreum was more effective in conidial inhibition of pathogen as crude MeOH the effective dose (ED50) was 0.16mg/ml. However, testing mixed all crude extracts as crude hexane, crude EtOAc and crude MeOH of Aloe vera, Turmeric, Ch. globosum and Ch. cupreum significantly inhibited conidial production of C. musae SKU-1 were 60.25-89.66%, also all crude extracts significantly inhibited mycelial growth of C. musae SKU-1 in banana fruits were 18.55%-44.61%.